PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEETS PADA MATERI KOORDINAT KARTESIUS UNTUK PESERTA DIDIK KELAS VIII MTsN 1 MATARAM TAHUN PELAJARAN 2024/2025 - Aulia, Sri Rahmatul; Sridana, Nyoman; Junaidi, Junaidi; Arjudin, Arjudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media e-LKPD based liveworksheets on Cartesian coordinate material for eighth grade students in junior high school. The method used in this study is Research and Development (R&D) with 3D research steps (define, design, and develop). The Data obtained from this study are qualitative data and quantitative data. Subjects in this study were students of Class VIII-7 in MTsN 1 Mataram totaling 30 people. Data analysis techniques to determine the validity and practicality of e-LKPD based liveworksheets were developed. The results showed that the media developed were (1) valid with a validity score of 0.82 with a valid Category; (2) practical with a percentage of 84% and obtained a very practical category. This shows that E-LKPD is valid and feasible to use in learning.